Synthesis of Secondary Amines with Long Chains Containing Ether Bonds - Xu, Haowei; Yang, Xiuying; Song, Lianjun; Wang, Xueyu; Li, Qiuju; He, Lanlan; Ding, Songdong (Synlett, 2022)
A novel class of secondary amines with long chains containing ether bonds were synthesized by a three-step protection–etherification–deprotection process from diethanolamine. The optimum reaction conditions were examined. This method has the advantages of simplicity, low cost, and high yield. Furthermore, some new downstream products (diglycolamides) were prepared from the ether-containing long-chain secondary amines as reactants, and their loading capacities in extractions of several metal ions were evaluated.
Keywords: amines; amino ethers; Williamson synthesis; diglycolamides; extractants